Humanização no contexto do trabalho em estratégia saúde da família: uma proposta convergente-assistencial - Vedootto, Denise de Oliveira (2017)
This study on the humanization in the context of the work in health aims to create opportunities for reflection on collective spaces about daily life, understand the subjective meanings and contribute to promote and enhance the inventive potential of subjects working in the health services, with a view to promoting health and quality of life at work. Given this, if established as research issues: What are the perceptions of health workers about the humanization in the work context? What are the possibilities of assistance actions with health workers in search of a movement of reflection about the humanization in the work context? Had as objectives: understand the perceptions of health workers about the humanization in the context of the work and carry out assistance actions with health workers in search of a movement of reflection about the humanization in the context of the work. The research was qualitative, with Convergent approach-Assistance. The scenario was a family health Strategy located in a municipality in the State of Rio Grande do Sul, Brazil. The participants were health workers inserted in this context, comprising a total of Fifteen participants. In this study, the data were produced through the technique of participant observation, semi-structured interview and convergence groups. After the analysis of the data was made up of the stages proposed by Convergent Healthcare Research method. The results indicate that the humanisation in the context of the work is intrinsic to subjective factors and elements that influence in the context of the work. The workers realize vertical relations between managers and workers and difficulties in the relationship with users, but there's a effectiveness and cooperation teamwork among employees of the ESF. Still, participants sit devalued in your most inappropriate, wage conditions, few training actions and excessive activities. Understand situations that may increase the pain/illness of the worker, with need for dialogue and discussion spaces. Convergence with the practice was accomplished through groups with workers of the ESF, which contributed to the enhancement of workers subjectivity from an interdisciplinary health care practice in groups of convergence with prominence of the subject. It is concluded that there is a need for research related to humanization in the context of the work, with the prospect of changes within the health services organizations, involving analysis of work processes, methods of work, to relate, to resist the adoecimentos to think, feel and live.